Immunomodulatory and anti-oxidant potential of Alpinia galanga Linn. rhizomes - Jain, Alok Pal; Pawara, Rajesh Singh; Lodhi, Santram; Singhai, Abhay K. (Pharmacognosy Communications)
Introduction: The plant Alpinia galanga Linn.(Zingiberaceae) is widely distributed in India. It is a perennial, aromatic and rhizomatous herb which is traditionally used as a carminative, stomachic, disinfectant, aphrodisiac and for the treatment of inflammation. The objective of present study is to evaluate the immunomodulatory and antioxidant effects of different extracts in a dose-dependent manner. Methods: Immunomodulatory activity was studied by examining T cell proliferation, splenocyte proliferation and by delayed type hypersensitivity reaction measurement. The antioxidant effect was observed by measuring lipid peroxidation (LPO), reduced glutathione (GSH) content and by determination of superoxide dismutase (SOD) and catalase (CAT) activities. Results: The flavonoid fraction of Alpinia galanga Linn. extract significantly stimulated (P <0.001) T cell proliferation and splenocyte proliferation in mice spleen at a dose of 100 mg/kg body weight of mice. The aqueous fraction had a lower stimulatory effect than the flavonoid fraction. The presence of quercetin in the flavonoid fraction was confirmed by chromatographic studies. The antioxidant level of the spleen cells also increased following treatment with the flavonoid fraction. Conclusion: In conclusion the flavonoid fraction of Alpinia galanga Linn. rhizomes have greater immunostimulating effects as well as antioxidant effects in mice.
Keywords: Alpinia galanga; galangal; immunomodulatory; antioxidant; flavonoid fraction; quercetin